(untitled) (Journal of Computational Mathematics, 2000)
This paper continues to construct and study the explicit compact (EC) schemes for conservation laws. First, we extend STCE/SE method on non-staggered grid, which has same well resolution as one in [1], and just requires half of the computational works. Then, we consider some constructions of the EC schemes for two-dimensional conservation laws, and some 1D and 2D numerical experiments are also given.